The Word in the Desert : Scripture and the Quest for Holiness in Early Christian Monasticism. - Burton-Christie, Douglas (Oxford University Press, 1994)
Growing scholarly debate in recent years on the religious world of late antiquity has focused new attention on the quest for holiness by early Christian monks known as the desert fathers. This book explores the setting within which their early monastic movement emerged.